Fenomena Industri Prostitusi Dalam Perspektif Subaltern - Launa (JIKA (Jurnal Ilmu Komunikasi Andalan), 2025)
The Indonesian prostitution industry is a historical phenomenon that has long historical roots. This phenomenon can be traced from the era of feudalism, colonialism to the era of independence. In the era of feudalism, women were positioned mythologically in a casteistic social system and patriarchal cultural format. This mythical construction succeeded in fully legitimizing the patriarchal and casteist system in controlling the image of women as subaltern entities. In the Dutch colonial era, the practice of commodification and commercialization of prostitutes was still limited by the supremacy of European values of rationalism, humanism and liberalism. Prostitutes are still seen as legal subjects who must be protected. Meanwhile, in the era of Japanese colonialism, the commodification and commercialization of prostitutes was more sadistic and brutal. In chauvinistic fascistic regimes such as Japan, women are not only seen as sexual objects, but as sex slaves. In the academic realm, the phenomenon of the prostitution industry will always be relevant to study. This is because various structural problems still surround prostitutes. Negotiating legal status, redefining the legality of the profession, articulating civil, political and socio-cultural rights, and reconstructing its existence as an informal economic sector that contributes to supporting the rate of national economic growth, are some of the academic questions that must be considered.